Historical perspectives on landscape and contemporary planning challenges : how landscape dynamics and the landscape’s past can contribute to current landscape planning - Brånhult, Anna (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2013)
This thesis seeks to explore how landscape dynamics and past landscape developments can contribute to current landscape planning. Through a literature review and a case study of the landscape’s historical development on the Bjäre peninsula, approaches for investigating and understanding past landscape developments and landscape dynamics are presented. Contemporary landscape planning challenges, such as the European Landscape Convention and the Swedish environmental objectives, are reviewed to outline the context in which landscape planning is practiced today, as well as to discuss how an analysis of historical landscapes can be used in current landscape planning. In the case study, changes in land use, landscape functions and driving forces are investigated, and furthermore discussed with the terminology of time-geography and the landscape as a budget frame. Some of the conclusions are that knowledge about landscape dynamics and the landscape’s past can contribute to the search for landscape identity, and the understanding of the landscape’s dependence on history, as well as its significance for the future. Identifying driving forces of landscape change can furthermore facilitate the task of reaching the goals in the European Landscape Convention and the Swedish environmental objectives. The landscape as a budget frame approach can by revealing the power struggle linked to landscape development, be used to discuss priorities in landscape planning, as well as their consequences.